2004
DOI: 10.1093/ps/83.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Incubation Temperature for Ostrich (Struthio camelus) Eggs

Abstract: The impact of incubation temperature on egg weight loss, embryonic mortality, incubation period, hatchability, and chick weight in 394 ostrich (Struthio camelus) eggs was studied. Eggs were obtained from 3 farms in Texas. Three incubation temperatures (36.5, 37.0, or 37.5 degrees C) with relative humidity ranging from 20 to 30% were used. Results showed that incubation of fertile eggs at 36.5 degrees C increased hatchability and incubation period in comparison with other treatments. The incidence of dead in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Increasing the incubation temperature from 36.0 to 37.2°C reduces hatchability from 73 to 44% (Stewart 1996). Similar results were found by Hassan et al (2004), who reported that mortality was increased at 37.5°C if compared to 36.5°C. The incubation period was reduced by about 2 days when the incubation temperature increased from 36.5 to 37.5°C (Hassan et al 2004).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Increasing the incubation temperature from 36.0 to 37.2°C reduces hatchability from 73 to 44% (Stewart 1996). Similar results were found by Hassan et al (2004), who reported that mortality was increased at 37.5°C if compared to 36.5°C. The incubation period was reduced by about 2 days when the incubation temperature increased from 36.5 to 37.5°C (Hassan et al 2004).…”
Section: Introductionsupporting
confidence: 89%
“…Similar results were found by Hassan et al (2004), who reported that mortality was increased at 37.5°C if compared to 36.5°C. The incubation period was reduced by about 2 days when the incubation temperature increased from 36.5 to 37.5°C (Hassan et al 2004). However, Stewart (1996) noticed that increasing the incubation temperature from 35.0 to 36.7°C decreased the incubation period by 3 days.…”
Section: Introductionsupporting
confidence: 89%
“…An estimate of the upper thermal tolerance for short-time exposure in most species is 41°C, and for exposures lasting several hours it is 39°C (Webb 1987). In Ostriches, increased embryo mortality is reported at temperatures above 37.5°C (Hassan et al 2004;Ipek et al 2003) and reduced hatching success is reported at temperatures above 40°C (Deeming et al 1993). The high core temperatures of brown-painted eggs observed in this experiment (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum temperature for Ostrich egg incubation is 36.0-36.5°C (e.g. Deeming 1993; Hassan et al 2004), and incubation temperatures above 37.5°C increase the incidence of dead embryos (Hassan et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…African ostriches obtain most moisture from their food and tolerate low temperatures, but drinking is important to sub-adults and newly hatched chicks are unable to thermoregulate (Brown and Prior, 1999). Industrial incubation studies indicate the importance of controlling necessary egg water loss and avoiding temperatures below 36 C (Hassan et al, 2004). The larger size of Struthio anderssoni eggs compared to S. camelus (Lowe, 1931) suggests increased egg and body size as a cold adaptation.…”
Section: Ydmentioning
confidence: 99%